0616 Self-Reported Sleep Inertia in the Hypersomnia Foundation Registry. (27th April 2018) - Trotti, L M; Ong, J; Plante, D; Powell, D; Bliwise, D L
Abstract: Introduction: Sleep inertia is well-defined experimentally in normal subjects. Although it is reported to occur commonly in patients with idiopathic hypersomnia, it has been less well-defined across hypersomnia conditions. Methods: The Hypersomnia Foundation, in consultation with authors (LMT, DLB), created a questionnaire of hypersomnolence symptoms and recruited participants. Questionnaires were completed online or via mail, using the Coordination of Rare Diseases at Sanford (CoRDS) rare-disease registry platform. Participants (mean age 37.3 years, SD = 12.9; 84.4% female; 97.4% Caucasian) in the registry with physician-diagnosed Idiopathic Hypersomnia (IH) (n = 294), Narcolepsy Type I (NT1) (n = 39) or NT2 (n = 33) reported categorical frequencies of 5 symptoms related to clinically-relevant sleep inertia. We collapsed categories of response and defined sleep inertia by whether each occurred nearly every day or more. Differences across groups were compared using Chi-square or Fisher exact test, as appropriate. In the case of significant differences, pairwise comparisons via Chi-square were performed with Bonferroni correction for multiple comparisons. Results: Features of sleep inertia were common among those with IH: (a) Not feeling rested after night sleep (97.5%); (b) Difficulty with morning awakening (82.5%); (c) Not feeling rested after a nap (73.8%); (d) Trouble functioning with normal alertness upon awakening (64.5%); and (e) Needing multiple alarms (57.2%). There was a main effect of group for each of the five sleep inertia features considered separately (all p-values below 0.01). All sleep inertia features except (e) were more frequently present in IH than NT1. Differences between IH and NT2 were significant for greater sleep inertia in the IH group on features (a), (c), and (e). Conclusion: Features of sleep inertia are widespread in people with IH, more so than in NT1. Somewhat more overlap of symptomatology between patients with IH and NT2 was present. The apparently greater phenomenological similarity between NT2 and IH implies that biomarkers should be more similar between these 2 diagnostic groups, rather than when compared to NT1. Further development of objective markers of sleep inertia in clinical settings should validate these findings. Support (If Any): K23-NS083748 (LMT).